The impact of the covid-19 pandemic on diabetes care: the perspective of healthcare providers across Europe. Issue 2 (April 2023) - Van Grondelle, S.E.; Van Bruggen, S.; Rauh, S.P.; Van der Zwan, M.; Cebrian, A.; Seidu, S.; Rutten, G.E.H.M.; Vos, H.M.M.; Numans, M.E.; Vos, R.C.
Abstract: Aims: Covid-19 caused changes on the delivery of diabetes care. This study aimed to explore perceptions of healthcare providers across Europe concerning 1) the impact of covid-19 on delivery of diabetes care; 2) impact of changes in diabetes care on experienced workload; 3) experiences with video consultation in diabetes care. Methods: Cross-sectional survey among healthcare providers in the Netherlands, United Kingdom, Turkey, Ukraine and Sweden, with a focus on primary care. Results: The survey was completed by 180 healthcare providers. During the COVID-19 pandemic 57.1% of respondents provided less diabetes care and 72.8% observed a negative impact on people with diabetes. More than half of respondents (61.9%) expressed worries to some extent about getting overloaded by work. Although the vast majority considered their work meaningful (85.6%). Almost half of healthcare providers (49.4%) thought that after the pandemic video-consultation could be blended with face-to-face contact. Conclusions: Less diabetes care was delivered and a negative impact on people with diabetes was observed by healthcare providers. Despite healthcare providers' feeling overloaded, mental wellbeing seemed unaffected. Video consultations were seen as having potential. Given the remaining covid-19 risks and from the interest of proactive management of people with diabetes, these findings urge for further exploration of incorporating video consultation in diabetes care. Highlights: During the COVID-19 pandemic less diabetes care was delivered by healthcare providers. Healthcare providers observed a negative effect of the COVID-19 pandemic on people with diabetes. Most healthcare providers worried about getting overloaded by work during the COVID-19 pandemic. Video consultations in primary diabetes care were seen as having potency by healthcare providers